Supply chain management : in theory and practice - Jespersen, Birgit Dam (Copenhagen Business School Press, 2005)
Annotation "The book presents a picture of state of the art within Supply Chain Management. It has a strategic focus and advocates a contingency approach to supply chain integration. Supply Chain Management has a theoretical foundation in transaction cost theory and the network approach." "The book can be used in teaching logistics and supply chain management courses, but also by logistics managers and SCM professionals when implementing the SCM concept in their own organisations."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Keywords: Business logistics.; Purchasing -- Management.; elektronické knihy; electronic books